Probiotic (Lactobacillus casei) Encapsulation Using the Method of Spray Drying with Combined Prebiotic from Iles-Iles (Amorphopallus oncophyllus) and Protectant Agent (Skim Milk, Gum Arabic, Maltodextrin) - Aloysius Prima Cahya; Meidi Syaflan; Ngatirah Ngatirah (Indonesian Food and Nutrition Progress, 2018)
The aims of this research were to know the effect of combine iles-iles (refined starch, whole iles-iles flour, and refined glucomannan) as encapsulating agent (capsule materials) and different protectant agents to get microcapsule synbiotic, which have the highest number of probiotic cells and high viability against low pH and bile salt. Design blocks complete with factorial design was used in the experimental design. The first factor was capsule materials with a concentration of 10% consisting of three material types: A1 (refined glucomannan), A2 (refined starch), and A3 (Iles-iles native). The second factor was protectant, protecting the probiotic bacteria during spray drying, used at concentration of 5% consisting of three substances i.e. B1 (skim milk), B2 (maltodextrin), and B3 (gum arabic). Using protectant agents on the MRS for the growth of L. casei resulted no effects against the numbers of LAB (lactic acid bacteria), density, moisture content, and hygroscopicity; however, it had influence on yield and solubility. The best use based on the reduction of LAB numbers were flour and gum Arabic which was significant compared to other fractions.Keywords: iles-iles, glucomannan, starch, protectant agent, symbiotic LAB